Tax planning in multinational corporations after the discussions referred to immorality of base erosion and profit shifting (BEPS): With focus on Starbucks Corporation - María Guadalupe Robles (University of Applied Sciences Mainz, 2018)
Tax planning is a crucial strategy that management can display in order to increase the net profit of the companies, by reducing tax expenses (Randeberg/Selvik, 2014). This is particularly significant for multinational corporations (MNCs), due to their possibility to take advantage of the different tax rates existing in the various countries where they operate (Krens, 2013). Even though most of the utilized practices were legal, they were increasingly discussed and accused of being immoral. Governments were urged by the public to take action. As a result, MNCs may possibly change their concept of tax planning and comportment. As one of the public actions, the "House of Commons Public Accounts Committee" In the United Kingdom suggested in 2012 that some large MNCs were using the tax legislation in an unintended way. Through tax planning, they managed to make huge profits and still pay very low amounts of taxes. From that moment on, base erosion and profit shifting (BEPS) has been a controversial topic in the international taxation field all around the world. This paper uses the case of Starbucks corporation to analyze to which extent the utilization of aggressive tax planning strategies has decreased since the immorality of BEPS was stated by the "House of Commons Public Accounts Committee". To this end, the financial statements of the years 2010 to 2015 are analyzed for four companies of the Starbucks group.
Keywords: 650